Nanofibrous bio-inorganic hybrid structures formed through self-assembled peptide (FKFSFEFEFKFK): article - Mat Nasir, Rian Aidil; Tan, Huey Ling; Mulana, Farid (2017)
Self-assembling peptides have gained a lot attention as its abilities been revealed in which can spontaneously experience self-organization into well-ordered structures. Consequently, it promotes another road for the creation of biological materials.In the past years,traditional therapeutic strategies for injuries requiring bone regeneration have relied on the use of autografting. However, problems resulting from donor-site morbidity and patient discomfort have led to the exploration of a variety of peptide-based and other hybrid materials for use as synthetic biocompatible matrices for bone regeneration. Since this revelation, different classes of short peptides have been fabricated with wide applications which include bone regeneration, reparative medicine, tissue designing, and drug delivery. This project involves discovering how nanofibrous bioinorganic hybrid structures can be formed through self-assembled peptide specified (FKFSFEFEFKFK). One of the ultimate goal is to observe the morphology and characterize the nanofibrous hybrid structures formed. This is done by synthesizing and characterizing the hydroxyapatite (HAp) at the first place.After that,followed by mineralization of HAp with the self-assembled peptide (FKFSFEFEFKFK) resulting nanofibrous hybrid structures to be formed. These structures are then analysed using sodium iodide and distilled water as their parameters on structural component. Several equipment and tools were involved for the analysis such as Fourier Transforms Infrared spectroscopy (FT-IR), X-ray diffractor (XRD) and Geology Microscope for characterization purposes.The application of nanofiber hybrid structures for biomimicry of bone recovery also will be further discussed in next section. Upon completion of these project, the finding may be useful to solve problems regarding fabrication of biomaterial and address the role of self-assembled together with HAp as inorganic material on biomineralization.